Income Analysis of Catching Equipment Business Revenue in Kampung Laut Village, Tanjung Jabung Timur District - Besse Jamaliatul Adawiyah; Wiwaha Anas Sumadja; Indra Sulaksana; M. Hariski; Rifli Rindes; Bagus Pramushinto (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2025)
This study aims to determine the income of traditional fishermen with splints in the village of Kampung Laut, Tanjung Jabung Timur Regency. This research was conducted on March 24 – April 03, 2022. This research is a survey research. The types of data collected are primary data and secondary data. Data collection techniques were carried out by direct interviews with splint fishermen with questions made in the form of research questionnaires. Determination of research respondents based on the Proposive Sampling method on 9 fishermen for 10 days/trip. Fishermen's income is calculated by looking at working capital/operational costs, catch and selling price. Analysis of the data used includes total costs, revenues, revenues and R/C ratio. The splints caught in the waters of Kampung Laut are Gulamah Fish (Johnius trachycephalus), Sembilang Fish (Paraplotosus albirabris), Mullet (Mugil cephalus), Tongue Fish (Cynoglossus lingua), Striped Shrimp (Parapenaeopsis sculptilis), Lime Shrimp (Matapenaeus brevicornis), Trash fish (Thryssa cuvier), eel (Gymnothorax dorsalis), puffer fish (Aratutron nigropunchtatus). The results showed that the average income of fishermen with splints was Rp.785.180/trip, with operational costs of Rp.264.319/trip, resulting in a net income of Rp.520.861/trip for fishing gear. in the waters of Kampung Laut using a profit-sharing system of 60:40 (2 crew members) where the income of the fisherman/captain is Rp. The fishing effort using this splint fishing gear obtained a B/C ratio value of 1.97. The conclusion of this study is that the fishing effort in the waters of Kampung Laut with splint fishing gear is profitable and feasible to run. The income received by the owner fishermen is quite good because it can cover the operational costs incurred by the ship owner.